The Effectiveness of Interdental Brushes for Biofilm Microbiocenosis Control: A Comparative Analysis and Practical Recommendations - Golinka Ольга; Melikova Катерина (Actual Dentistry, 2026)
Introduction. Biofilm accumulation in proximal tooth areas remains a key etiological factor in the development of gingivitis, periodontitis, and proximal caries. Despite the regular use of manual or electric toothbrushes, up to 40% of tooth surfaces remain insufficiently cleaned — predominantly in the interdental spaces. Consequently, the implementation of auxiliary interdental hygiene aids is critical, and interdental brushes demonstrate the highest clinical efficacy among them in the routine control of microbiocenosis. The aim of the study. The aim of this work is to analyze current scientific data on the effectiveness of interdental brushes in biofilm control compared to other interdental hygiene aids and to formulate practical recommendations for dentists and dental hygienists. Results. An analysis of current scientific publications has shown that interdental brushes are an effective tool for biofilm control in proximal areas. Most studies demonstrated a significant reduction in both the plaque index and the gingival bleeding index compared to using a toothbrush alone. Comparative data indicate that interdental brushes are more effective in reducing gingival inflammation than dental floss in patients with open interdental spaces. Our own clinical observations confirmed a positive dynamic of clinical parameters and an increase in patient compliance, provided that the size of the brush was individually selected. Conclusions. Interdental brushes are an effective tool for biofilm control in proximal areas, contributing to the reduction of gingival inflammation and playing an important role in the prevention of dental caries and periodontal diseases. Their use is appropriate provided there is an individual selection, proper patient training in application techniques, consideration of the clinical situation, ergonomics of the product shape, and regularity of use. Interdental brushes are of particular importance for patients with dental implants, orthodontic appliances, and orthopedic restorations as an essential component of supportive individual oral hygiene.